Analysis of Internal Nutrient Load Dynamics from the Sediment in Lake Ziway - Tibebe, Dessie; Zewge, Feleke; Lemma, Brook; Kassa, Yezbie (International Journal of Chemistry and Materials Research, 2020)
Lake Ziway is shallow freshwater located in Northern part of Ethiopian Rift Valley. Expansions of the flower industry, widespread fisheries, intensive agricultural activities, fast population growth lead to deterioration of both water and sediment qualities and depletion of aquatic biota. The main objective of this study is to evaluate the internal nutrient load dynamics from the sediment. Nutrients in sediment samples were analyzed according to the standard procedures outlined in EPA, 1994 and phosphorus release rate were estimated with THE methods described in Steinman, et al. [3]. The results of sediment depth profile analyses showed that the mean concentrations of SRP, TP, NO3-N, NO2-N and TN were 27.7, 62, 5.28, 8.51 and 1733 mg/kg, respectively in dry season, and 21.2, 73, 7.99, 28.4, 24.2 and 1750 mg/kg, respectively in wet season. The values for all the studied nutrients distribution were higher at sediment top surface and decline with depth of the sediment profiles in most of the sampling sites and seasons. The results of the seasonal evaluation of phosphorus flux from lake sediments showed that sediments were sources of phosphorus. The findings from the current study indicate that internal sources of nutrients to Lake Ziway vary across time and space. Understanding this variation and internal nutrient load is important in developing mitigation and restoration strategies for the lake ecosystems.